Structural insights into the elevator-like mechanism of the sodium/citrate symporter CitS - Ji Won Kim (Nature Portfolio, 2017)
Abstract The sodium-dependent citrate transporter of Klebsiella pneumoniae (KpCitS) belongs to the 2-hydroxycarboxylate transporter (2-HCT) family and allows the cell to use citrate as sole carbon and energy source in anaerobic conditions. Here we present crystal structures of KpCitS in citrate-bound outward-facing, citrate-bound asymmetric, and citrate-free inward-facing state. The structures reveal that the KpCitS dimerization domain remains stationary throughout the transport cycle due to a hydrogen bond network as well as extensive hydrophobic interactions. In contrast, its transport domain undergoes a ~35° rigid-body rotation and a ~17 Å translocation perpendicular to the membrane to expose the substrate-binding site alternately to either side of the membrane. Furthermore, homology models of two other 2-HCT proteins based on the KpCitS structure offer structural insights into their differences in substrate specificity at a molecular level. On the basis of our results and previous biochemical data, we propose that the activity of the 2-HCT CitS involves an elevator-like movement in which the transport domain itself traverses the lipid bilayer, carrying the substrate into the cell in a sodium-dependent manner.